Biochemical characterization of argininosuccinate lyase from M. tuberculosis: significance of a c‐terminal cysteine in catalysis and thermal stability. Issue 11 (16th October 2017) - Mishra, Archita; Surolia, Avadhesha
Abstract: Arginine biosynthesis pathway is crucial to the survival and pathogenesis of Mycobacterium tuberculosis ( Mtb ). Arginine is a critical amino acid that contributes to the inflection of cellular immune responses during pathogenesis. Argininosuccinate lyase from Mtb ( Mt ArgH), the last enzyme in the pathway, catalyzes the production of arginine from argininosuccinic acid. Mt ArgH is an essential enzyme for the growth and survival of M. tuberculosis . We biochemically characterized Mt ArgH and deciphered the role of a previously unexplored cysteine (Cys 441 ) residue at the C‐terminal region of the protein. Chemical modification of Cys 441 completely abrogated the enzymatic activity suggesting its involvement in the catalytic mechanism. Replacement of Cys 441 to alanine showed a striking decrease in the enzymatic activity, while retaining the overall secondary to quaternary structure of the protein, hence corroborating the involvement of Cys 441 in the process of catalysis. Interestingly, replacement of Cys 441 to serine, showed significant increase in activity, as compared to the wild‐type Mt ArgH. Inactivity of C 441 A and elevated activity of its conservative mutant (C 441 S) confirmed the participation of Cys 441 in the Mt ArgH activity. We also, observed that C 441 S mutant has higher thermal stability and maintains significant activity at high temperatures. This is in concordance with our observation that Cys 441 in Mtb is replaced by a serine in the ArgH from thermophilic microorganisms. Furthermore, we also propose a potential feedback mechanism, wherein the Cys 441 is covalently modified to S‐(2‐succinyl) cysteine (succination) by one of the products, fumarate, thereby inactivating Mt ArgH. These insights into the mechanism of Mt ArgH activity unravel novel regulations of arginine biosynthetic pathway in Mtb . © 2017 IUBMB Life, 69(11):896–907, 2017